Impact of organoleptic properties on pediatric antibiotic compliance: a comparative study of three commonly prescribed co-amoxyclav suspensions in India - Bhawe, Amit; Moidutty, Sajitha; Surve, Chaitali; Panda, Madhumita; Mohanasundaram, Senthilnathan (International Journal of Contemporary Pediatrics, 2025)
Background: Palatability is a crucial factor influencing adherence of medication in pediatric populations, especially for oral antibiotic suspensions. This study aimed to evaluate and compare the organoleptic properties of three co-amoxyclav 457 mg formulations: Product A (Advent), Product B (Comparator 1) and Product C (Comparator 2) in 55 healthy school-going children aged 6 to 9 years. Methods: Each product was administered at 15–20-minute intervals and responses were recorded using a structured questionnaire that included behavioural analysis, taste discrimination, ranking and compliance perception. Results: Product A showed the highest acceptability, with 94.5% of children displaying favourable facial expressions and 100% accepting the product. Based on taste, 91% rated product A as excellent or good, compared to 67% for product B and 82% for product C. Additionally, 85% of participants described product A’s taste as sweet, with a fruity orange aftertaste. Smell ratings were also highest for Product A, with 89% rating it excellent or good, versus 71% for product B and 73% for product C. Regarding aftertaste, 78% found product A sweet, while about 55% found products B and C sweet. Overall, 57% of children preferred product A and more than 90% assured they would complete the course if prescribed this formulation. Conclusions: These findings highlight the importance of organoleptic properties in pediatric antibiotic formulations. By considering organoleptic properties during prescribing, healthcare providers can significantly enhance adherence, leading to improved treatment outcomes and a reduced risk of antimicrobial resistance.